Single-crystalline Pd square nanoplates enclosed by 100 facets on reduced graphene oxide for formic acid electro-oxidation. Issue 99 (14th November 2016) - Jiang, Yi; Yan, Yucong; Chen, Wenlong; Khan, Yousaf; Wu, Jianbo; Zhang, Hui; Yang, Deren
Abstract : 100 faceted Pd nanoplates were prepared on reduced graphene oxide and exhibited substantially enhanced catalytic properties towards formic acid oxidation. Abstract : Single-crystalline Pd square nanoplates enclosed by 100 facets were generated on reduced graphene oxide and exhibited the substantially enhanced properties for the formic acid oxidation reaction. The combination of carbonyl groups formed on the surface of annealed graphene oxide and Br − ions played important roles in this synthesis.